Space disorders existencial crises in the liquid modernity - Berti, Gustavo (2012)
This essay evaluates the conditions of possibility in the presence of panic attacks and other disorders of the specialty from its phenomenological approach based on the hermeneutics of Martin Heidegger and revalidated in therapeutic practice. From this approach, the psychic pathology is seen as the irruption of the nothing in the Desein and the mutual aid is proposed as an alternative for solving these crises.